ANALISIS PENGELOLAAN ZAKAT PADA BAZNAS KOTA JAMBI - Amelia Novia Pitri; Eja Armaz Hardi; Solichah Solichah (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
The National Zakat Amil Agency is a zakat management organization formed by the government, consisting of elements of the community and government with the task of collecting, distributing and utilizing zakat in accordance with religious provisions. The Jambi City National Zakat Amil Agency (BAZNAS) carries out the task of managing zakat at the city level. This research aims to analyze zakat management which consists of planning, collecting, distributing, utilizing, reporting and supervising zakat in the Jambi City Baznas, to find out the obstacles that exist in the zakat management process in the Jambi City Baznas, and to find out the benefits after the community receives financial assistance. zakat from Baznas Jambi City. This research uses a descriptive qualitative method. To reveal this problem in depth and comprehensively, the author collected data by means of observation, interviews, documentation and triangulation. The results of the research show that, the implementation of zakat management at Baznas Jambi City is in accordance with management theory, where in management theory management consists of planning, collection, distribution, utilization, reporting and supervision. The implementation of zakat management at the Jambi City Baznas has met the standards of this management theory. So the implementation of zakat management at Jambi City Baznas is good, even though zakat funds are still lacking, Jambi City Baznas continues to distribute zakat funds to those in need so that the benefits of zakat funds in Jambi City can be felt by the community as intended by the zakat law.